Educational Game Design “Napak Tilas Panji Asmorobangun” in “Wayang Beber” Story - Alby Aruna; Nadiya Faydinda Putri Ishlah; Laila Inayah; Abdul Rahman Prasetyo (STAI Miftahul Ula Nganjuk, 2021)
The process of digitizing historical learning in Indonesia in times of emergency, the learning media used today is predominantly conventional. With regard to conventional learning media, the contribution of digitalization of learning media to provide direction for modernization of historical learning media in solving the lack of exploration, elaboration, critical thinking skills, the flow of historicallearning concepts, and the lack of touch to local wisdom is needed. Using ADDIE Model, the design of the educational game of Panji Asmorobangun in the story of puppets beber Pacita nfocus is implemented in Vocational HighSchool (SMK) State 1 Pacitan gained 87.5% in the validation of media experts, 91.1% in validation of material experts. With regards to expert validation, this media also scored 87.22% in a group trial of 50 students andsaid it is very feasible to implementunder the name of superpanji media branding. The historical learning media of Panji Asmorobangun figures in puppet stories beber Pacitan Regency supports the game flow process with (High Order Thinking Skils) HOTS through the 5M tifical design approach(enjoy,menanya, collect information, socialize, and communicate).